"A TAX ON THE MANY, TO ENRICH A FEW": JACKSONIAN DEMOCRACY VS. THE PROTECTIVE TARIFF. Issue 2 (1st June 2015) - Belko, William S.
Abstract : The core concepts underlying Jacksonian Democracy—equal protection of the laws; an aversion to a moneyed aristocracy, exclusive privileges, and monopolies, and a predilection for the common man; majority rule; and the welfare of the community over the individual—have long been defined almost exclusively by the Bank War, which commenced in earnest with the election of Andrew Jackson in 1828. Yet, this same rhetoric proved far more pervasive and consistent when one considers the ardent opposition to the protective system. Opponents of the protective tariff, commencing with the Tariff of 1816 and continuing unabated to the Walker Tariff of 1846, thus contributed directly to the development of Jacksonian Democracy, and, by introducing and continually employing this language, gave to the tariff debates in the United States a unique angle that differed from the debates in Europe.